Morphology‐Performance Relationships in High‐Efficiency All‐Polymer Solar Cells. Issue 3 (2nd October 2013) - Zhou, Nanjia; Lin, Hui; Lou, Sylvia J.; Yu, Xinge; Guo, Peijun; Manley, Eric F.; Loser, Stephen; Hartnett, Patrick; Huang, Hui; Wasielewski, Michael R.; Chen, Lin X.; Chang, Robert P. H.; et al.
<x xml:space="preserve">Abstract</x> Careful selection of processing solvents to tune optimal active layer morphology in a donor‐acceptor copolymer blend [PTB7:P(NDI2OD‐T2)] yields bulk heterojunction microstructures with intradomain percolative pathways and enhanced charge transport. Such microstructures afford all‐polymer solar cells with power conversion efficiencies as high as 2.7%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>